Using social network analysis to identify stakeholders' influence on energy efficiency of housing. (8th June 2017) - Zedan, Sherif; Miller, Wendy
Energy-efficient housing is a product that integrates various stakeholders' tasks throughout the different stages of its life cycle. The relationships between these stakeholders impact on the degree of knowledge sharing and informed decision-making and can potentially enhance or lower the energy efficiency of the product – the house. This article uses a social network analysis (SNA) approach to visualize the social networks of the stakeholders of a number of owner-occupied housing case studies in Australia. The aim is to analyse, contrast and quantify the degrees of connectivity and centrality of the housing stakeholders to identify which groups have more connectivity in the stakeholders' network of energy-efficiency housing and consequently more potential to influence the energy efficiency outcomes and which practices are more likely to enhance transparency and information sharing that is essential for producing energy-efficient housing.